Evaluation of cookies made with bean flour - Sánchez-Toledano, Blanca; Cruz, Raquel; Salgado-Beltran, Lizbeth; Espinoza, Jose (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The common bean (Phaseolus vulgaris L.) is a legume rich in protein, carbohydrates, vitamins, and minerals that can be used for food processing. The objective of this study was to evaluate the acceptance of cookies made from bean flour by consumers in Zacatecas, Mexico, for which four formulations of cookies with different combinations of bean flour were prepared. The information was obtained from a sample of 398 consumers over 18 years of age in Zacatecas, Mexico, and was analyzed by multidimensional scaling. In general, the quality attributes relevant to consumers were size, aroma, sweetness, texture, color, consistency, and flavor. Cookie number 873 obtained higher consumer acceptance and its ingredients were 90 % bean flour, 10 % whole wheat flour and walnut. Therefore, the results of this research showed that cookies made from bean flour could be a feasible alternative that allows providing more nutritious food to the Mexican population.